2002
DOI: 10.1038/sj.npp.1300038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repetitive Transcranial Magnetic Stimulation (rTMS) in the Treatment of Affective Disorders

Abstract: Transcranial magnetic stimulation (TMS) is a relatively noninvasive technique to interfere with the function of small cortical areas through currents induced by alternating magnetic fields emanating from a handheld coil placed directly above the targeted area. This technique has clear effects on a whole range of measures of brain function and has become an important research tool in neuropsychiatry. More recently, TMS has been studied in psychiatry mainly to assess its putative therapeutic effects in treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…The neurobiological effects of this novel therapeutic tool in humans are not sufficiently explained so far, but it has repeatedly been reported that the mesolimbic dopaminergic system plays an important role in mediating the mood improvements in depressed patients (review: Padberg and Möller, 2003;Schlaepfer et al, 2003). Recently, we found an increase in DA release in NAS, striatum, and hippocampus in response to acute rTMS , which could be replicated by others (Kanno et al, 2004;Zangen and Hyodo, 2002).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The neurobiological effects of this novel therapeutic tool in humans are not sufficiently explained so far, but it has repeatedly been reported that the mesolimbic dopaminergic system plays an important role in mediating the mood improvements in depressed patients (review: Padberg and Möller, 2003;Schlaepfer et al, 2003). Recently, we found an increase in DA release in NAS, striatum, and hippocampus in response to acute rTMS , which could be replicated by others (Kanno et al, 2004;Zangen and Hyodo, 2002).…”
Section: Introductionsupporting
confidence: 64%
“…Although in most cases not anatomically precise (Herwig et al, 2001), rTMS effects in clinical studies most probably relate to frontal forebrain stimulation (review: eg Padberg and Möller, 2003;Schlaepfer et al, 2003). Consequently, to reliably investigate the underlying neurobiological effects in animal models, the adoption of equivalent stimulation conditions is indispensable.…”
Section: Rtms In Rat Studiesmentioning
confidence: 99%
“…A more comprehensive conceptualization of depression that inspires specific, targeted neuromodulatory intervention might allow better treatment modalities for depression associated with fewer side effects. Indeed, there were no side effects in any of our DBS patients.Other brain stimulation techniques exist that use electrical currents or magnetic fields, such as electroconvulsive therapy, repetitive transcranial magnetic stimulation, and vagus nerve stimulation, all of which have antidepressant effects (George et al, 2000;Schlaepfer and Kosel, 2004;Schlaepfer et al, 2003). However, like antidepressants, these methods are also less focused, affect larger areas of the brain not necessarily associated with depression, and induce side effects to various degrees.…”
mentioning
confidence: 99%
“…В качестве альтернативы высокочастотной рТМС не-которыми исследователями [150] предлагалось использо-вать низкочастотную стимуляцию правой DLPFC. Одна-ко результаты проведенных двойных слепых плацебо-контролируемых исследований оказались противоречи-выми.…”
Section: депрессияunclassified